Exceptional anatomical variation of the upper biliary confluence - Montano, Daniel; Perdomo, Mauro; Giroff, Nicolás; Ruso Martínez, Luis (Cirugía del Uruguay, 2023)
Variations in the formation of the upper biliary confluence and their frequency must be known to ensure optimal results in liver surgery and avoid biliary surgical injuries.